APLIKASI PENDATAAN KELUAR MASUK PENUMPANG KAPAL MELALUI SELAT MALAKA DI PULAU BENGKALIS BERBASIS WEB: SHIP PASSENGER EXIT DATA COLLECTION APPLICATION THROUGH THE MALAKA STRAIT ON BENGKALIS ISLAND BASED WEB - Reza Suci Nazirah; Diah Angraina Fitri; Fajar Ratnawati (JISTECH: Journal of Information Science and Technology, 2018)
The ship is one of sea transport that is widely used by the community particularly wholived in the Islands for example Bengkalis.Bengkalis Regency, which has a layout is verystrategic because it is directly adjacent to the Strait of Malacca until passed by theinternational shipping lanes.Logging current ship passengers still are manual that istyped using a typewriter and delivered straight to the Immigration Office.Thereforecreated an application web-based ship passengers logging by using MySQL as thedatabase that runs on a xampp server so it makes it easy to ship party in merekappassengers and immigration data to view and check out their report data accuratelypassengers. The design method used in this study is UML which consists of use caseand activity diagrams.